PERENCANAAN DAN PENGENDALIAN PRODUKSI AGREGAT PADA USAHA TEDUNG UD DWI PUTRI DI KLUNGKUNG - Juliantara, I Komang; Mandala, Kastawan (E-Jurnal Manajemen; Vol 9 No 1 (2020)DO - 10.24843/EJMUNUD.2020.v09.i01.p06, 2020)
Production planning and control is very important to minimize the occurrence of excess product inventory so that the demand season is low and vice versa there is a shortage of products during the high demand season. The purpose of this study is to determine and determine the amount of production with minimal costs at UD Dwi Putri Klungkung. This research was conducted on building products using an aggregate production planning system while the data used in this study were sales data for one year, production capacity, overtime costs, storage costs and labor costs. Based on the results of the study indicate that the estimated number of products produced during the next year is as many as 31,531 units, which are based on the exponential smoothing method. This method is used, because the exponential smoothing method gives results that have the smallest standard error with MAD value of 208.812, MSE value of 61843.5 and MAPE value of 7.97%. Aggregate planning strategy with chase strategy produces a total production cost of Rp. 242,995,500.00, where the total cost lower, compared to the total production cost with a strategy level of Rp. 254,337,081.00. Keywords: Forecasting, Aggregate Planning, Chase Strategy, Strategy Level